CHEMICAL CHARACTERISTICS OF A NATURAL FLAVORING AGENT MADE FROM SQUID HEAD FLOUR (Loligo sp.) USING A FOOD DEHYDRATOR - Khoeruddin Wittriansyah; Ari Kristiningsih; Jenal Sodikin (Saintek Perikanan : Indonesian Journal of Fisheries Science and Technology, 2026)
Squid heads are typically discarded and treated as waste. They contain protein and glutamic acid, which have potential as natural flavor enhancers. Utilizing squid head waste as a flavor enhancer is a solution for managing fishery waste and an alternative to synthetic flavor enhancers. The objective of this study is to analyze the chemical composition of a natural flavor enhancer made from squid head waste flour with added maltodextrin, dried using a food dehydrator. The research method used in this study is a laboratory experiment employing a Completely Randomized Design (CRD) with 4 treatments and 3 replicates, varying the addition of squid head flour and maltodextrin. The amount of squid head flour for each treatment is P1 (15 g), P2 (30 g), P3 (45 g), and P4 (60 g). Maltodextrin was added at 2.5% of the total ingredient weight for each treatment: P1 (1 g), P2 (1.375 g), P3 (1.75 g), and P4 (2.125 g). The food dehydrator was set to 60°C for 40 hours. The chemical analysis included protein, glutamic acid, and moisture content. The results showed that the highest protein content was found in P3 (39.60%) and the lowest in P1 (23.58%). The lowest moisture content was found in P4 at 5.16%. The moisture content results did not meet the requirements of SNI 01-4273-1996 (beef flavor enhancer), which specifies a maximum value of 4%. Meanwhile, the highest glutamic acid content was found in P3 (3.52%) and the lowest in P1 (1.93%).